PENGARUH KOMITMEN ORGANISASI, BUDAYA ORGANISASI DAN KOMPENSASI TERHADAP KINERJA KARYAWAN BAGIAN MARKETING (Studi Pada Bank Pembiayaan Rakyat Syariah (BPRS) Bhakti Sumekar Semenep) - jurnalmap map; Jamal Syafriyanto; Chamariyah ÔÇì; Subijanto ÔÇì (Program Pascasarjana Universitas Wijaya Putra Surabaya, 2019)
ABSTRACT This research was conducted at the Sharia Community Financing Bank (BPRS) Bhakti Sumekar Sumenep. with a total sample of 50 people. The results of the study show that: 1). Simultaneously, organizational commitment, organizational culture and compensation have a very significant influence on employee performance. 2). Partially, organizational commitment, organizational culture and compensation have a significant influence on the Employee Performance of the Sharia People's Financing Bank (BPRS) Bhakti Sumekar Sumenep. Thus, it can be said that all independent variables partially have a significant influence on the performance of employees of the Sharia People's Financing Bank (BPRS) Bhakti Sumekar Sumenep and the organizational commitment variable has a dominant influence in influencing the performance of employees of the Syariah Financing Bank (BPRS) Bhakti Sumekar Sumenep. Keywords: Organizational Commitment (X1), Organizational Culture (X2), Compensation (X3) and Employee Performance (Y)